Anatomy of the iliopsoas notch and its relationship with morphology of the proximal femur - Benes, Michal; Kunc, Vojtech; Nanka, Ondrej; Kachlik, David; Bartak, Vladislav (Surgical and radiologic anatomy, 2024)
PURPOSE: Discrepancy between the morphology of the acetabular margin and the design of hemispheric acetabular cups used in total hip arthroplasty may produce postoperative hip pain due to an iliopsoas impingement at the iliopsoas notch. This study aimed to determine the anatomical features of the iliopsoas notch in the Central European sample, and to test whether the morphology of the proximal femur affects the size of the iliopsoas notch. METHODS: The sample was composed of 40 matched pairs of dry hip bones and corresponding femora. The depth and length of the iliopsoas notch were measured and correlated with the available demographic data. The anthropometric parameters of the proximal femur were calculated using image-analysis software, and their association with the measurements of the iliopsoas notch was tested. RESULTS: The iliopsoas notch was present in all specimens and featured four morphological configurations: curved (61.3%), angular (16.2%), irregular (16.2%), and straight (6.3%). Its size was found to be larger in males (P = 0.014 for depth, P < 0.001 for length). No significant difference existed between the sides. The height and age of the specimens did not correlate with the size of the iliopsoas notch. Furthermore, neither the femoral neck version, the lesser trochanteric version, nor the angle between the neck of the femur and the lesser trochanter influenced the dimensions of the iliopsoas notch. CONCLUSION: The iliopsoas notch is a consistent landmark of the acetabulum, although its anatomical appearance is widely variable. The iliopsoas notch arrangement cannot be predicted perioperatively based on the morphology of the proximal femur. The various shapes and sex-related differences detected in this study could be used for designing new hip implants or could be utilized during cup positioning in total hip arthroplasty.
Keywords: dolní končetina; Humans; Acetabulum; Psoas valley; Arthroplasty, Replacement, Hip; náhrada kyčelního kloubu; lidé; femur; Lower Extremity; kosterní svaly; Psoas U; Femur; Male; Iliopsoas notch; Muscle, Skeletal; Anterior labral sulcus; acetabulum; Total hip arthroplasty; mužské pohlaví